Pulmonary alveolar proteinosis in children: a case series - Tabatabaei, Seyyed Ahmad (Medknow Publications, 2010)
Pulmonary alveolar proteinosis, (PAP) is a rare disease of unknown etiology, characterized by accumulation of intraalveolar proteinaceous material which is rich in lipid and positive on periodic acid-Schiff stain. Two clinically different pediatric types have been defined as congenital PAP which is fulminant and fatal, and a late-onset PAP which is similar to the adult form and less severe. Eight children with late-onset PAP were hospitalized from 1998 to 2005 in Mofid Children Hospital. Characteristics of these patients and the methods of diagnosis and treatment are presented in this case series.